Identification and Isolation of Cardiac Fibroblasts From the Adult Mouse Heart Using Two-Color Flow Cytometry - Stellato, Mara; Czepiel, Marcin; Distler, Oliver; Błyszczuk, Przemysław; Kania, Gabriela (Frontiers in Cardiovascular Medicine, 2019)
Background Cardiac fibroblasts represent a main stromal cell type in the healthy myocardium. Activation of cardiac fibroblasts has been implicated in the pathogenesis of many heart diseases. Profibrotic stimuli activate fibroblasts, which proliferate and differentiate into pathogenic myofibroblasts causing a fibrotic phenotype in the heart. Cardiac fibroblasts are characterized by production of type I collagen, but non-transgenic methods allowing their identification and isolation require further improvements. Herein, we present a new and simple flow cytometry-based method to identify and isolate cardiac fibroblasts from the murine heart. Methods and Results Wild-type and reporter mice expressing enhanced green fluorescent protein (EGFP) under the murine alpha1(I) collagen promoter (Col1a1-EGFP) were used in this study. Hearts were harvested and dissociated into single cell suspensions using enzymatic digestion. Cardiac cells were stained with the erythrocyte marker Ter119, the pan-leukocyte marker CD45, the endothelial cell marker CD31 and gp38 (known also as podoplanin). Fibroblasts were defined in a two-colour flow cytometry analysis as a lineage-negative (Lin: Ter119–CD45–CD31–) and gp38-positive (gp38+) population. Analysis of hearts isolated from Col1a1-EGFP reporter mice showed that cardiac Lin–gp38+ cells corresponded to type I collagen-producing cells. Lin–gp38+ cells were partially positive for the mesenchymal markers CD44, CD140a, Sca-1 and CD90.2. Sorted Lin–gp38+ cells were successfully expanded in vitro for up to four passages. Lin–gp38+ cells activated by Transforming Growth Factor Beta 1 (TGF-β1) upregulated myofibroblast-specific genes and proteins, developed stress fibres positive for alpha smooth muscle actin (αSMA) and showed increased contractility in the collagen gel contraction assay. Conclusions Two-colour flow cytometry analysis using the selected cell surface antigens allows for the identification of collagen-producing fibroblasts in unaffected mouse hearts without using specific reporter constructs. This strategy opens new perspectives to study the physiology and pathophysiology of cardiac fibroblasts in mouse models.